1513: The Hospitallers of Rhodes Appeal for Support against the Ottomans at the Fifth Lateran Council (Transmediterranean History, 2025)
This article describes an address made by Giovanni Battista de Gargiis, a member of the Knights Hospitaller, at the eighth session of the Fifth Lateran Council in December 1513. In it, he appealed to both the papacy and Europe’s secular rulers to send aid to the Hospitallers on Rhodes to counter the threat of an imminent Ottoman invasion. Drawing on this source, this article discusses the emergence of the Hospitallers in Jerusalem and the Holy Land, and their eventual transfer to the island fortress of Rhodes. In doing so, it considers the broader geopolitical consequences of the Hospitallers’ presence in the eastern Mediterranean, with an eye to the order’s interactions with Latin-Christian rulers in Europe, as well as Muslim rulers in the Levant and North Africa. The source is held to be unusual for the way it draws on a broader body of political and religious ideas and imperatives in an effort to rally European-Christian support for the defence of Rhodes and the conquest of Muslim-held territories, such as Constantinople and Jerusalem.
Keywords: Hospitallers; Rhodes; crusades; legitimisation; Ottomans; threat; papacy; diplomacy; Holy Land; Fifth Lateran Council